Deriving European Tantalum Flows Using Trade and Production Statistics. (23rd January 2017) - Deetman, Sebastiaan; van Oers, Lauran; van der Voet, Ester; Tukker, Arnold
Summary: Even though tantalum has a high economic importance and is associated with armed conflict, the use of tantalum throughout the supply chain of importing economies is not well understood. This article adds to existing qualitative descriptions of the tantalum supply chain by performing a quantified substance flow analysis (SFA) of tantalum for Europe in the year 2007. The exercise is meant to show how readily available statistical information could be used along with simple and transparent assumptions on product composition and allocation, to yield an enabling and visual representation of the supply chain for critical materials. The case of tantalum shows some surprising results. First of all, this study shows that tantalum in computer hard disks and artificial joints may be more relevant than found in previous studies. Further, we find that the tantalum consumption in Europe may be larger than expected based on geological survey reports, attributed to a high fraction of tantalum being imported in subcomponents and final products. Further research is needed to substantiate this claim, but what is clear is that a detailed SFA provides valuable insights into the consumption of tantalum as a critical material, throughout the stages in the supply chain related to the production and use of tantalum‐containing products. The exercise also allowed production of waste generation profiles and enabled identification of e‐waste as an important focus group in order to improve tantalum recycling rates and eventually to reduce society's dependence on scarce or conflict‐related raw materials.